Strategi Produksi Kerupuk Kulit Ikan Patin dalam Memenuhi Permintaan dan Peningkatan Pendapatan pada CV. Raja Patin Indonesia dengan Menggunakan Metode Pentahelix - Sri Dewi Anggraini; Muhammad Yafiz; Rahmat Daim Harahap (Universitas Muhammadiyah Surabaya, 2023)
AbstractThis research departs from the problem that what production strategy can be carried out to meet demand and increase income in catfish skin cracker products. The aim is to find out and analyze the production strategy of catfish skin crackers in meeting demand and increasing income at CV. Raja Patin Indonesia using the triple helix method. This research approach is qualitative. The types of data used are primary data and secondary data. Methods of data collection are done directly or through interviews. The results of the study indicate that the product strategy that must be carried out by the company is to maintain the quality of taste and the quality of the products produced. Price is one of the demand factors,therefore CV. Raja Patin Indonesia produces crackers at very friendly prices for all walks of life. The characteristic taste that is specially formulated from selected Indonesian spices is one of the identities of these skin crackers. The government, academics, and SMEs have so far synergized in terms of developing SMEs and SMEs, especially those in North Sumatra. The government, which has provided some training, capital, and also facilities to introduce products, is one of the efforts being made. Academics by becoming mentors at MSME seminars or even conducting research related to UKM are also one of the efforts that have been made by academics as research development centers.The absorption of labor by the company to improve the economic welfare of the community or reduce existing unemployment is one of the efforts made by the company to empower the surrounding community.The media is no less important in the development of a business, the media is a liaison and interaction between government, business, academia, and also the community. With the media, a product can be known by many people who live outside the city and even the world.Keywords: Production Strategy, Demand, Revenue, and Pentahelix.